EFFECTS OF PRESIDENT UMARU MUSA YAR’ADUA’S 7-POINT AGENDA ON AGRICULTURAL DEVELOPMENT AND FOOD SECURITY IN NIGERIA - Gadzama, Ishaku Usman (European Scientific Journal, ESJ, 2013)
This paper examines the effects of President Umaru Musa Yar’Adua’s 7-point agenda on agricultural development and food security. The UN population divisions have estimated that the world population would increase to 8.9 billion in 2050 and half of this will be concentrated in eight countries including Nigeria. The food sub-sector of Nigerian agriculture parades a large array of staple crops, made possible by the diversity of agro-ecological production systems. The major food crops that are produced are: cereals (sorghum, maize, millet, and rice); tubers (yam and cassava); legumes (groundnut and cowpeas) and others (fruits and vegetables). These commodities are of considerable importance for food security, expenditures and incomes of households. However, the highest incidence of undernourishment is found in sub-Saharan Africa, where one in every three persons suffers from chronic hunger. It is also noted that in the 21st century, because of decreasing fertility rates, the number of people who have attained 60 years old or more will triple in three out of four developing countries. The total number of older people in developing countries is expected to rise from 8 per cent in 2000 to 20 per cent in 2050. This development will put serious strains on human security as people’s ability to move out of poverty and cope with crisis will be undermined. A good performance of an economy in terms of per capita growth may therefore be attributed to a well-developed agricultural sector capital. Hunger has threatened the lives of many people in developing countries. In fact, there is a widespread of hunger, malnutrition and food insecurity despite the fact that there are adequate food resources in Nigeria. The paper therefore investigates the Nigerian government, agricultural development and food security, United Nations Organizations and human security approach, the 7-point agenda of President Yar’ Adua and its effects on agricultural production and food security in Nigeria, synergy between agricultural development and food security and production of availability of food in deficit countries. The paper further advocates that a major policy implication of this is that concerted effort should be made by policy makers to increase the level of productivity of agricultural sector in Nigeria by improving expenditure on the sector so as to boost the growth of the economy. Since the agricultural sector is the major contributor to GDP in Nigeria which is capable of changing social indicators of the economy, policies aimed at adequate financing of the sector by government in order to boast its output, may be a way forward.